Pharmacological modulation of cell functional activity with valproic acid and erythropoietin - Polina A. Golubinskaya; Marina V. Sarycheva; Svetlana Y. Burda; Maksim V. Puzanov; Natalya A. Nadezhdina; Vladimir F. Kulikovskiy; Sergey V. Nadezhdin; Michail V. Korokin; Yuriy E. Burda (Belgorod National Research University, 2019)
Introduction: Valproic acid (VA) is carboxylic acid with a branched chain, which is used as an antiepileptic drug. Valproic acid influence on cells in vivo: VA, which is an antiepileptic drug, is also a teratogen, which causes defects of a neural tube and an axial skeleton, although the mechanisms are not yet fully clear. Valproic acid influence on mesenchymal stem cells (MSC) in vitro: It is shown that valproic acid reduces the intracellular level of oxygen active forms. Valproic acid effect on tumor cells: VA inhibits tumor growth through several mechanisms, including the cell cycle stop, differentiation induction and inhibition of growth of tumor vessels. Valproic acid influence on enzymes: It affects mainly GSK-3. Valproic acid influence on animals' cells: It is shown that VA can significantly improve an ability to develop in vitro and improve nuclear reprogramming of embryos. Erythropoietin (EPO): Is an hypoxia-induced hormone and a cytokine, which is necessary for normal erythropoiesis. EPO is widely used in in vitro experiments. Conclusion: Thus, the influence of VA and EPO on cells can be used in cell technologies.